ANALISIS EVALUASI PROGRAM PEMBENTUKAN KADER JUMANTIK SEBAGAI UPAYA PENGENDALIAN DBD DI DESA BANDAR SETIAKECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - NURUL RAHMAH SIREGAR; NABILA PELANGI UMARI; ZULIA WIRDANI PUTRI NST; TIARA NOVIA FAJAR AMINAH; CUT IVA AULIA; RIZKY NOOR AL IMRAN (LP2MTBM MAKARIOZ, 2022)
Dengue disease is a dengue virus infection disease that is still a health problem for the Indonesian people. The disease is caused by the Dengue virus which is transmitted by the mosquito vector Aedes aegypty through bites. Based on data from the Bandar Khalipah health center, the cumulative number from January to August 2022, the number of dengue hemorrhagic fever (DHF) sufferers in Bandar Setia Village reached 39 cases. The purpose of jumantic cadre creating is to improve the knowledge and skills of cadres so that they become pioneers in moving the community to continue to carry out PSN 3M plus independently. This research uses methods in the form of lectures and discussions. The results of the jumantic cadre empowerment activities in Bandar Setia Village, Percut Sei Tuan District, so that the formation of a jumantic cadre group in Bandar Setia Village, there was an increase in the knowledge of jumantic cadres in an effort to prevent dengue disease.